GERAKAN SOSIAL BARU â€œKOMUNITAS KETIMBANG NGEMIS BALI (KNB)â€ DI KOTA DENPASAR - Ari Wirati, Ni Made; Kebayantini, Ni Luh Nyoman; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2021)
This research seeks to discuss the movement to appreciate the elderly working and participation in campaigning anti-begging actions by Ketimbang Ngemis Bali in Denpasar City. The research used qualitative and descriptive-explanative approaches to explain the efforts, obstacles and impacts of the Ketimbang Ngemis Bali social movement. The theory used is a new social movement in the form of mobilization of resources by Anthony Oberschall. The results showed that Ketimbang Ngemis Bali's efforts were realized through bernas activities, donation distribution, groboli, entrepreneurship programs, promotion of solia businesses and socialization of beggars and the community. In practice, Ketimbang Ngemis Bali's actions experienced various obstacles such as low physical community participation to the lack of beggar response to socialization activities. The impact of Ketimbang Ngemis Bali's action has been felt by various parties such as solia, members, volunteers and followers along with a positive response from the community. Keywords: Appreciation, Komunitas Ketimbang Ngemis Bali, Solia, Participation.